International initiatives influence on local government sustainability web-disclosures - Joseph, Corina; Taplin, Ross (Emerald Group Publishing Ltd, 2012)
Purpose – The purpose of this paper is to investigate the influence of the international initiative (Agenda 21) on the level of sustainability disclosures by Malaysian local authority websites. Design/methodology/approach – The influence of the LA 21 program is considered using the institutional isomorphism and a mixed method research design. Findings – Content analysis of website disclosures by 139 local authorities shows that it is the council's commitment to the LA 21 program by explicitly stating this commitment on their website that is linked to higher sustainability disclosures and not the council's actual involvement in the program. Interview findings provided evidence of both normative and mimetic isomorphism in relation to the LA 21 program. The paper identifies the multiple effect of isomorphism for the LA 21 program using both quantitative and qualitative research designs. Practical implications – The LA 21 program is an example of an international commitment by many countries towards improving sustainability reporting. This paper shows how the decision by Malaysia to agree to this program has improved website sustainability reporting by Malaysian local authorities, starting from the LA 21 pilot project involving only a few authorities to involvement by all 145 authorities. Originality/value – This adds to a growing body of literature in public sector disclosure and sustainable development by showcasing how an international initiative can impact sustainability reporting at the local level.